Oxytocin reduces anger bias, harm-intention recognition, and self-focus in behavioral variant frontotemporal dementia: a randomized double-blind placebo-controlled crossover trial - Colonnello, Valentina; Capellari, Sabina; Guarino, Maria; Parchi, Piero; Sambati, Luisa; De Matteis, Maddalena; Stanzani-Maserati, Michelangelo; Russo, Paolo Maria; Mattarozzi, Katia (Frontiers in Aging Neuroscience, 2026)
ObjectiveTo explore the effects of oxytocin administration on social cognition and social engagement in patients with behavioral variant frontotemporal dementia.MethodsIn a within-subject, double-blind, placebo-controlled, randomized crossover trial, patients with behavioral variant frontotemporal dementia completed the primary outcome measures, facial emotion and intention recognition tasks. Secondary outcomes included evaluation of drug safety and tolerability and changes in social engagement, assessed through caregiver ratings of social behavior. Exploratory outcomes included anger-bias in emotion misclassification and a LIWC-based analysis of speech during a semi-structured interview.ResultsOxytocin was safe, well-tolerated, and improved social engagement in naturalistic contexts: caregivers reported positive changes, including increases in awareness, spontaneous initiative, socio-affective engagement, and reductions in appetite/impulsivity. Exploratory analyses suggested that oxytocin reduced the tendency to misclassify fearful and sad expressions as angry and reduced the use of first-person pronouns during spontaneous speech. However, the study detected no improvements in the emotion recognition and observed decreased accuracy in recognizing harmful intentions.ConclusionExploratory findings suggest that oxytocin reduces threat-bias, promotes social engagement, and decreases self-focused language, while no improvements were detected on experimental measures of social cognition. The results highlight the safety and potential of innovative oxytocin-based pharmacological interventions and the value of incorporating naturalistic assessments, such as ecological social interactions and language analysis, to optimize the detection of therapeutic effects in neurodegenerative diseases. Oxytocin may hold promise for enhancing social engagement in behavioral variant frontotemporal dementia, although its effects on language use and higher-order cognitive processes require further investigation.